Raw potato starch diet supplement in weaned pigs could reduce Salmonella Typhimurium infection by altering microbiome composition and improving immune status - Yi, Seung-Won; Lee, Han Gyu; Kim, Eunju; Jung, Young-Hun; Bok, Eun-Yeong; Cho, Ara; Do, Yoon Jung; Hur, Tai-Young; Oh, Sang-Ik (Frontiers in Veterinary Science, 2023)
Salmonella enterica serovar Typhimurium (ST) is one of the causative agents of gastroenteritis in pigs. Pigs fed a diet supplemented with raw potato starch (RPS) have improved gut health by the alteration of the microbiota composition and production of short-chain fatty acids (SCFAs). This study aimed to evaluate the effects of RPS supplementation in reducing infection severity and fecal shedding in ST-infected pigs. The weaned experimental pigs were divided into two groups: CON (n = 6) fed a corn/soybean-based diet and TRT (n = 6) supplemented with 5% RPS. After 21 d, the pigs were inoculated with ST, and their body weight, clinical signs, and fecal shedding of ST were monitored for 14 d. At 14 d post-inoculation (dpi), the jejunum, cecum, ileum, and colon tissues were collected from euthanized pigs, and histopathological lesions and cytokine gene expression were compared. Additionally, blood samples at 2 dpi were analyzed for gene ontology enrichment. Moreover, the gut microbiome was analyzed using 16S rRNA metagenomic sequencing, and the SCFA concentration was measured using gas chromatography. The average daily weight gain was significantly higher in TRT than in CON during the ST infection period; however, histopathological lesion scores were significantly lower in TRT than in CON. The relative abundance of nine genera of butyrate- and acetate-producing bacteria significantly increased in TRT compared with that of only two acetate-producing bacteria in CON. Among the genes involved in the immune response, IL-18 expression level was significantly lower in the jejunum and colon in TRT than in CON. Furthermore, Reg3γ expression was significantly different in the cecum and colon of both groups. In conclusion, a diet supplemented with RPS in weaned pigs could result in predominance of butyrate- and acetate-producing bacteria, reducing the severity of ST infection by improving the immune status.